Blackleg in cattle: A case report of fetal infection and a literature review. (September 2017) - Abreu, Camila C.; Edwards, Erin E.; Edwards, John F.; Gibbons, Philippa M.; Leal de Araújo, Jeann; Rech, Raquel R.; Uzal, Francisco A.
Clostridium chauvoei causes blackleg in cattle. The disease has been reported worldwide, and although it can be prevented by vaccination, sporadic cases and occasional outbreaks still occur. We describe a case of blackleg in a 2-y-old, pregnant Gyr cow with in utero transmission to the fetus. The cow had characteristic gross and microscopic lesions of blackleg including widespread necrohemorrhagic and emphysematous skeletal and myocardial myositis, and fibrinous pericarditis. Her uterus contained a near-term, markedly emphysematous fetus with skeletal muscle and myocardial lesions similar to those seen in the dam. Histopathology of dam and fetal tissues revealed numerous gram-positive bacilli, many of them with sub-terminal spores, in multiple tissues. These bacilli were identified as C. chauvoei by immunohistochemistry. Anaerobic culture and fluorescent antibody tests performed on skeletal muscle from both the dam and fetus were positive for C. chauvoei, confirming a diagnosis of blackleg. Blackleg is a so-called endogenous infection, and the currently accepted pathogenesis involves ingestion of spores that are transported to muscle tissues where they lie dormant until anaerobiosis prompts germination. Germinating bacteria are histotoxic, producing severe, local necrosis and ultimately lethal toxemia. This model, however, has not been confirmed experimentally and also fails to explain some cases of the disease. A presumptive diagnosis of blackleg is based on clinical, gross, and histologic findings. Diagnostic confirmation necessitates the detection of C. chauvoei by culture, PCR, or immunodetection methods.